Edukasi Anti Bullying Sebagai Penguatan Pendidikan Karakter Bagi Siswa Di Guntur Demak - Illiyyah, Niswatun; Putri, Maudy Ananda; Mahfiroh, Luthfiatunisa Aulia; Rofiq, M. Khoirur (Universitas Gajah Putih, Indonesia, 2023)
Schools are one of the many places where there are many problems of bullying or bullying. Sekolah Dasar Negeri 2 Guntur is one of the schools whose students are not spared from bullying cases. The period of State Elementary School (SDN) is the beginning for children to adapt to the surrounding environment, and during this State Elementary School period children still have a tendency to imitate things that happen around them. Therefore, the purpose of this activity is to provide knowledge and character building for participants who are students of SDN 2 Guntur and find a model of bullying prevention through character education and school roles. Character education is an important role in shaping children's morals. Through character education from an early age, it is hoped that it can produce a generation of good, competent, and dignified nations. The result of the activities that have been carried out is a change in awareness, knowledge and attitudes that show the prevention of bullying. Where previously there were still many students who did not know what bullying is. After being presented about bullying and how to prevent it, students became more careful not to bully.